2005
DOI: 10.1210/jc.2004-1251
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin, Peptide YY, Glucose-Dependent Insulinotropic Polypeptide, and Hunger Responses to a Mixed Meal in Anorexic, Obese, and Control Female Adolescents

Abstract: To determine whether peptide YY (PYY), ghrelin, glucose-dependent insulinotropic polypeptide (GIP), and satiety responses to food intake are impaired in anorexia or obesity, we studied 30 female adolescents with anorexia nervosa [body mass index (BMI) 16.3 kg/m2], obesity (BMI 34.3 kg/m2), or normal weight (BMI 20.2 kg/m2). PYY, ghrelin, GIP, insulin, and glucose concentrations and four markers of satiety were measured for 240 min after a mixed meal. The area under the curve for glucose was similar in obese (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
160
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(198 citation statements)
references
References 55 publications
28
160
9
1
Order By: Relevance
“…This study showed that the PYY was comparable between lean and obese people, despite the fact that the obese people were more insulin resistant and produced significantly more insulin in response to glucose [27]. Another study found no correlation between circulating PYY or insulin levels in normal, obese and anorexic subjects [44].…”
Section: Clinical Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…This study showed that the PYY was comparable between lean and obese people, despite the fact that the obese people were more insulin resistant and produced significantly more insulin in response to glucose [27]. Another study found no correlation between circulating PYY or insulin levels in normal, obese and anorexic subjects [44].…”
Section: Clinical Studiesmentioning
confidence: 63%
“…Although these studies suggest that PYY1-36 or PYY3-36 do not have a role in glucose homeostasis, it is important to highlight that PYY levels were measured in obese people that already have high fasting insulin [5], in diabetic subjects that were already insulin resistant [17] or in anorexic subjects who had an eating disorder and were likely to have an altered PYY response in addition to having decreased baseline insulin levels [44]. Indeed it is feasible that these obese, diabetic and anorexic subjects may have decreased sensitivity to PYY1-36 and PYY3-36, which normally function to influence glucose-stimulated insulin secretion or insulin sensitivity, respectively.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Other studies have founded that postprandial GIP response was inversely related to the subsequent feeling of satiety (5,12,13). On the other hand, positive (14) or neutral (9,10,15) correlation between postprandial GIP and satiety were also observed.…”
Section: Introductionmentioning
confidence: 89%
“…36 In most patients there is a negative correlation between fasting ghrelin levels and body mass index, reflecting the presence of an adequate physiological response, with low or high ghrelin levels in the context of positive or negative energy balance, respectively. Consequently, fasting ghrelin levels are usually low in obese subjects compared with controls, 37 although levels rise after diet induced weight loss. 35,38 In contrast, patients with nervous anorexia have high fasting ghrelin levels.…”
Section: Ghrelinmentioning
confidence: 99%